2009
DOI: 10.1016/j.bbrc.2008.11.053
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr virus-derived EBNA2 regulates STAT3 activation

Abstract: The Epstein-Barr virus (EBV)-encoded latency protein EBNA2 is a nuclear transcriptional activator that is essential for EBV-induced cellular transformation. Here, we show that EBNA2 interacts with STAT3, a signal transducer for an interleukin-6 family cytokine, and enhances the transcriptional activity of STAT3 by influencing its DNA-binding activity. Furthermore, EBNA2 cooperatively acts on STAT3 activation with LMP1. These data demonstrate that EBNA2 acts as a transcriptional coactivator of STAT3.3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 24 publications
1
25
0
1
Order By: Relevance
“…The activation of Stat3 can be mediated by extrinsic or intrinsic cues. EBV, which is intimately-associated with NKTCL, was thought to be one such extrinsic activator of STAT signaling [68]. The novel fusion gene LEP, which produces a protein product that was found to activate JAK2/3 and STAT3 by stimulating tyrosine phosphorylation [69], was identified in one of 34 Koreans.…”
Section: Stat3mentioning
confidence: 99%
“…The activation of Stat3 can be mediated by extrinsic or intrinsic cues. EBV, which is intimately-associated with NKTCL, was thought to be one such extrinsic activator of STAT signaling [68]. The novel fusion gene LEP, which produces a protein product that was found to activate JAK2/3 and STAT3 by stimulating tyrosine phosphorylation [69], was identified in one of 34 Koreans.…”
Section: Stat3mentioning
confidence: 99%
“…It has been shown that several tumor-related viruses, including HBV, are related to the activation of STAT3 (Migone et al, 1995;Sun and Steinberg, 2002;Choudhari et al, 2007;Muromoto et al, 2009). Indeed, constitutively activated STAT3 is crucial for compensating hepatocyte turnover and leads to advanced fibrosis and cirrhosis, which are the key clinical risk factors for HCC development (Subramaniam et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…2A, the LIF-induced DNA-binding activity of STAT3 was enhanced by EBNA2 expression, consistent with a previous report. 10) Importantly, coexpression of SMRT with EBNA2 resulted in a reduction of the enhanced DNA-binding activity of STAT3. Taken together, these results show that SMRT regulates enhanced STAT3-mediated transcriptional activation by EBNA2.…”
Section: Smrt Regulates Ebna2-mediated Enhanced Stat3mentioning
confidence: 99%
“…11,12) Expression vector for epitope-tagged-EBNA2 was previously described. 10,13,14) Anti-EBNA2 monoclonal antibody (mAb) was purchased from Advanced Biotechnologies Inc. (Maryland, U.S.A.). Anti-Myc and anti-STAT3 antibodies were obtained from Santa Cruz Biotechnology (Santa Cruz, CA, U.S.A.).…”
mentioning
confidence: 99%
See 1 more Smart Citation